Large cohort study finds a statistically significant association between excessive crying in early infancy and subsequent ear symptoms. (12th February 2014) - Hestbaek, Lise; Sannes, Marianne Myhre; Lous, Jørgen
Abstract Aim The diagnosis of infantile colic is based on excessive crying. However, several causal factors can account for this disconcerting, nonspecific symptom. The main aim of this study was to investigate a possible association between excessive crying during the first 6 months of life and subsequent ear problems. Methods Data from a cohort study of 26 983 Danish children were used. Mothers participated in four telephone interviews and one questionnaire and provided information on crying in the first 6 months of life and ear symptoms at the ages of 6 months, 18 months and 7 years. Results There was a statistically significant association between excessive crying in infancy and subsequent ear symptoms. A gradual increase in subsequent ear problems was seen with increasing crying time at all the data collection times. Conclusions The results of this study suggest a possible link between excessive crying and ear infections. Whether such a link is causal or due to common underlying factors is still unknown. We recommend thorough ear examinations in children with symptoms compatible with infantile colic.